2018
DOI: 10.1080/1068316x.2018.1552757
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ perceptions of children’s referentially ambiguous responses

Abstract: The present study examined adults’ (N = 295) interpretations of child witnesses’ referentially ambiguous “yes” and “no” responses to “Do You Know/Remember (DYK/R) if/whether” questions (e.g., “Do you know if it was blue?”). Participants were presented with transcripts from child sexual abuse cases modified based on question format (DYK/R vs. Direct) and child response type (Yes, No, I don’t know) in a between subjects design. We assessed whether adults recognized that children’s ambiguous responses were unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Furthermore, findings revealed no significant differences in children’s accuracy when answering Why or How Come questions. Although past studies have combined these two questions in analyses, as there are no differences in the productivity of children’s responses (see Andrews et al, 2016), research also suggests that semantic differences in question forms can influence how the question is interpreted, and in turn the accuracy of children’s responses (see Evans et al, 2014; Wylie et al, 2019). Therefore, given the differing interpretations of Why (e.g., accusatory and critical) and How Come questions (e.g., surprise and disbelief), we examined these questions separately, with the goal of informing best practices for phrasing questions to young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, findings revealed no significant differences in children’s accuracy when answering Why or How Come questions. Although past studies have combined these two questions in analyses, as there are no differences in the productivity of children’s responses (see Andrews et al, 2016), research also suggests that semantic differences in question forms can influence how the question is interpreted, and in turn the accuracy of children’s responses (see Evans et al, 2014; Wylie et al, 2019). Therefore, given the differing interpretations of Why (e.g., accusatory and critical) and How Come questions (e.g., surprise and disbelief), we examined these questions separately, with the goal of informing best practices for phrasing questions to young children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, past research has grouped Why and How Come questions together in analyses, as there were no differences in the productivity of their responses (e.g., Andrews et al, 2016). However, research suggests that minor differences in semantics can influence interpretations of the question and in turn the accuracy of children’s responses (e.g., Evans et al, 2014; Wylie et al, 2019). For example, How Come questions may express greater surprise or disbelief, whereas Why questions are more accusatory or critical which may lead children to justify their actions rather than accurately describe the cause of the event (Walker, 1999).…”
Section: The Current Studymentioning
confidence: 99%
“…Research examining children's “no” responses to DYK/R if/whether questions has not found a systematic pattern in whether children are answering the implicit or explicit question (Evans et al, 2017). “Yes” responses are less problematic, because experimental evidence suggests that when children respond “yes” to DYK/R if/whether questions, they are answering the implicit question (Ahern et al, 2016), and this is consistent with adults' typical interpretation of children's “yes” responses (Wylie et al, 2019).…”
mentioning
confidence: 84%
“…Past research by Wylie et al (2019) examining jury‐eligible adults' interpretations of ambiguous responding found that adults rarely recognized the ambiguous nature of unelaborated responses to DYK/R if/whether questions. In that study, adults were presented with child testimony that included referentially ambiguous “yes” and “no” responses to DYK/R if/whether questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation